The Impact of Consumers’ Loneliness and Boredom on Purchase Intention in Live Commerce During COVID-19: Telepresence as a Mediator - Peng, Chen; Liu, Zhikun; Lee, Jong-Yoon; Liu, Shanshan; Wen, Fang (Frontiers in Psychology, 2022)
This paper examines the relationship between consumer loneliness, boredom, telepresence, influencer-brand image congruence and purchase intention by investigating consumers of live commerce during the COVID-19 period. Data were collected through an online survey of 550 consumers and analyzed by SPSS 26.0. The results showed that consumers' loneliness and boredom impacted consumers' purchase intention. Telepresence played a mediating role in the impact of loneliness and boredom on purchase intention. Influencer-brand image congruence played a moderating role in the impact of consumers' boredom on purchase intention. The study results contribute to the study of factors impacting consumers' purchase intention. In addition, this study can help live commerce merchants better understand the impact factors of consumers' purchase intention and contribute to the development of live commerce.